MANAJEMEN PEMBINAAN KOMPETENSI GURU MADRASAH ALIYAH BERBASIS PESANTREN - Wahyu Hidayat (Jurnal Pendidikan Islam, 2013)
This study is proposed to identify and analyse the development of planning, organization, implementation and evaluation of teacher competence Pesantren-based Madrasah Aliyah. The research site was Darul Arqam MA Muhammadiyah MAN Cipasung Garut and Tasikmalaya. This study utilized a qualitative approach. Data were collected through observations, interviews and documentation. Academic qualifications of teachers in the two madrasas generally have met the minimum educational qualification as mandated by Law number 14 of 2005 regarding Teachers and Lecturers. Planning for teacher competency training in both madrasah generally use 3 stages, namely: diagnosis, planning and preparation of documents. The authority to conduct the training is in the head of madrasah or the leader of pesantren. The implementation of the trainings done through the program for improving the academic qualification, certification, integrated training and supervision. Basic principles of this trating activity always refers to the Sunnah of the Prophet Muhammad and the tradition of the al-salaf as-shâlih. Evaluation was conducted conducted on aspects of teacher competence. The evaluation results were followed up by workshop, remedial and preventive programs in the form of workshops, repair and prevention.